Identifikasi Garis Pantai Zona Intertidal Menggunakan Citra ALOS PALSAR Studi Kasus Distrik Merauke Kabupaten Merauke - Basith, Abdul (2014)
Intertidal zones are areas that lie between the highest and lowest tide of coastal region. Forms of intertidal zones are affected by two factors: local tidal characteristics, i.e. tidal range, and the respective coastal topography, i.e. coastal slope. Coastal areas having large tidal ranges offer feasibility to study intertidal boundaries. District Merauke, West Papua, is well known to have large tidal range, 4-5 m, with coastal slopes ranges between 0-8 percent, categorized as ramps slope. This research is intended to identify coastlines defining intertidal zones using ALOS PALSAR imagery for identification of instantaneous shoreline, digital terrain model from SRTM for determining coastal slopes, and global tide model TPXO 7.1 for predicting tidal data at Merauke coast during the image acquisition. The results show that the length of identified instantaneous shoreline is 18.172,004 m. Meanwhile, the length of coastlines at high tide and low tide is 22.934,903 m and 30.242,489 m respectively. The area of identified intertidal zone is 4.587.826,299 m2 . The width of intertidal zone varies from 73,711 m to 1.375,933 m. There are locations at which the width of intertidal is not significant because their widths are less than 90 m, the resolution of SRTM. These locations generally have coastal slope more than 4.6 percent.